Analisis Strategi Persaingan PT Kalbe Farma Tbk - Aryanti, Jessica; Kaltum, Umi (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2023)
Competitive strategy analysis can be fundamental for responding to external conditions and increasing internal capabilities in generating a company’s competitive advantage. The purpose of this research is to determine the company's position in the industry as a basis for selecting alternative strategies so the company can strengthen its competitiveness and overcome its weaknesses in facing competitors. The methodology is descriptive qualitative research. Observation is done by data obtained from secondary sources. The analysis carried out includes: The Input Stage with Competitive Profile Matrix; The Matching Stage with Boston Consulting Group (BCG) Matrix and the Grand Strategy Matrix based on competitive analysis according to Porter's Five (Plus One) Forces; The Decision Stage with the Quantitative Strategic Planning Matrix (QSPM). Justification was carried out based on a Forum Group Discussion with several experts using the Delphi Method. The result shows that there is a change in competitive conditions, thus the market leader company, Kalbe Farma, needs to make strategic adjustments. In conclusion, the results of strategy alternatives’ formulation through BCG Matrix and Grand Strategy, as well as the selection of strategies using the QSPM show that the priority strategies for Kalbe Farma, respectively sorted from the most recommended are Market Penetration, Market Development, and Product Development.